The Web Content Style Guide: An Essential Reference for Online Writers, Editors, and Managers - McGovern, Gerry; Norton, Rob; O'Dowd, Catherine (Pearson, 2001)
As quality becomes ever more critical in differentiating successful websites, the need for a professional approach to your content is growing. The Web Content Style Guide provides a set of standards and rules to ensure consistent quality content and a flawless service to your readers.